Short-process preparation method of high-strength plastic titanium plate
Through a short process preparation method, including remelting and smelting, forging, hot rolling and deep cold rolling, the formation of titanium plates with multi-stage isomerial structures is solved, and the problems of poor performance stability and mismatch between strength and plasticity of TA18 titanium alloy material are achieved, and the excellent strength and plasticity of titanium plates are improved, and the production efficiency is improved.
Patent Information
- Application Number
- CN202411915460.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The high-strength TA18 titanium alloy materials prepared in the prior art have problems such as poor performance stability and mismatch between strength and plastic properties.
A short-process preparation method of high-strength plastic titanium plate is adopted, including two remelting and smelting, casting, forging and opening, hot rolling and multi-pass deep cold rolling, through these steps, forming a multi-stage heterogeneous structure synergistically strong plastic titanium plate.
The excellent strength and plasticity of the titanium plate are achieved, the problem of mismatch between strength and plastic properties is solved, and the two annealing processes in traditional technology are eliminated, which significantly shortens the production cycle and improves production efficiency.
Smart Images

Figure CN119702753A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium materials, in particular to a short-process preparation method of a high-strength plastic titanium plate. Background Art
[0002] Titanium alloys have excellent properties such as light weight, high specific strength, corrosion resistance, and high temperature resistance. They have broad application prospects in aerospace, shipbuilding and marine engineering, oil and gas extraction, metallurgy, medical treatment, sports and leisure, etc. Among them, TA18 alloy is a low-alloyed near-α titanium alloy with a nominal composition of Ti-3Al-2.5V. It has good room temperature and high temperature mechanical properties, corrosion resistance, and notch insensitivity. In early production, this alloy was developed for the application of aircraft pipeline boosting systems. In recent years, with the continuous demand of the aerospace industry for development goals such as lightweight, high speed, and long life, the requirements for the performance of TA18 alloy have continued to grow. However, the high-strength TA18 titanium alloy materials currently prepared still have problems such as poor performance stability and mismatch between strength and plasticity.
[0003] In order to solve the above problems, the patent with publication number CN112195364A discloses a high-temperature, high-strength titanium alloy and its processing method. The invention improves the strength of the titanium alloy through the preparation method of melting-forging-multiple hot rolling-heat treatment. However, recent studies have shown that, as Yang Jianchao [Yang Jianchao, Xi Jinhui, Yang Yashe, et al. Research and development and application of TA18 titanium alloy pipes for aerospace [J]. Titanium Industry Progress, 2014 (4): 6-10] said, since TA18 titanium alloy has very little β phase at room temperature, its strengthening method is mainly deformation strengthening. After processing and deformation, the plate can reach different strength levels by controlling the heat treatment temperature and time. However, the room temperature plasticity of titanium alloy will be seriously reduced during cold processing and deformation.
[0004] Therefore, it is necessary to design a method for preparing high-strength plastic titanium plates. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the present invention provides a short-process preparation method for a high-strength and plastic titanium plate. The titanium plate prepared by the preparation method of the present invention has excellent strength and plasticity.
[0006] In order to achieve the above object, the specific scheme adopted by the present invention is: A short-process preparation method for a high-strength plastic titanium plate mainly comprises the following steps: Step 1: placing the TA18 titanium alloy consumable electrode block in a vacuum consumable arc furnace for two remelting smeltings, and then casting to obtain a pure TA18 titanium ingot; Step 2: Heat the TA18 titanium ingot to 100-160°C above the β phase transition temperature and keep it warm for 1 hour, then forge and open the blank to obtain a blank; Step 3, heating the billet to the phase transition point of the α+β two-phase region, hot rolling using a four-roll reversible rolling mill, rolling the billet from 120.0 mm to 5.8 mm through 5-8 rolling passes, with a single rolling deformation of no more than 30%, and a total deformation of 95%, to obtain a titanium alloy plate; after rolling, the titanium alloy plate is surface polished and acid-alkali cleaned; Step 4: Perform multiple passes of deep cold rolling on the titanium alloy plate to obtain a titanium plate with a thickness of 2.4 to 4.8 mm.
[0007] Furthermore, in step one, the preparation method of the TA18 titanium alloy consumable electrode block is: mixing sponge titanium, aluminum beans and aluminum vanadium according to the atomic percentage of Ti:Al:V=96:2.5:1.5, and then pressing the mixed raw materials into a cylindrical electrode block, and then welding the electrode block into a consumable electrode block.
[0008] Furthermore, in step one, the first smelting voltage is 35V, the current is 2.5-3.5KA, and the vacuum degree is 1.0×10E-1Pa; the second smelting current is 4.0-5.0KA, and the vacuum degree is 1.0×10E-1Pa.
[0009] Furthermore, in step 1, the composition of the TA18 titanium ingot is, by mass fraction, 2.92% Al, 2.22% V, 0.025% Fe, 0.018% C, and the remainder is Ti and unavoidable impurities.
[0010] Furthermore, in step 4, the specific method of deep cold rolling treatment of the titanium alloy plate is: immersing the titanium alloy plate in liquid nitrogen for 20 minutes to 1 hour; deep cold rolling treatment of the titanium alloy plate at 77K, after 4-6 rolling passes, the total rolling deformation is 17%-60%.
[0011] Furthermore, the titanium alloy plate needs to be immersed in liquid nitrogen for 20 minutes to 1 hour before each rolling pass.
[0012] Beneficial effects:
[0013] (1) The present invention adopts dual-phase hot rolling and deep cold rolling processes to prepare a titanium plate with multi-level heterogeneous structure and synergistic strength and plasticity. The strengthening effect of the titanium plate is improved by fine grain strengthening in the fine grain zone and hindering dislocation movement by twinning in the coarse grain zone. The geometric required dislocations induced by deformation of the coarse grain and fine grain layered heterogeneous structure are used to improve the strain hardening ability of the titanium plate, thereby solving the bottleneck problem of the inversion of strength and plasticity of the titanium plate in the prior art.
[0014] (2) Compared with the prior art preparation process of "forging-hot rolling-annealing-multi-pass rolling-annealing", the present invention has the following beneficial effects: (I) The prior art, in which the forging process adopts the process of "high temperature-low temperature-high temperature-low temperature" to carry out multiple forgings at different temperatures to make blanks, although the purpose is to break the cast structure, but the large deformation operation in a specific direction inevitably leads to obvious anisotropy of the forged plate structure and performance in different directions. In addition, during flat anvil forging, there is a deformation dead zone in the contact area with the anvil surface. As the thickness of the forged plate decreases, the proportion of the deformation dead zone continues to increase, resulting in significant differences in the structure and performance of the edge and core of the forged plate thickness direction. The subsequent hot rolling process is due to the poor uniformity of the early forging structure, and the uniformity of the sheet structure and the performance improvement effect are also greatly reduced. Although the two annealing processes can eliminate some internal stresses and adjust the structure morphology, the process is relatively time-consuming and energy-consuming, which may not only lead to the loss of some strengthening effects, but also extend the production cycle and increase costs. Due to the unsatisfactory early organizational foundation, the refinement effect and dislocation distribution control of multi-pass rolling are far inferior to the effect of cold rolling based on the optimized organization of the present invention.
[0015] (II) From the working principle point of view, the present invention uses TA18 titanium alloy consumable electrode blocks as raw materials, performs two remelting smelting in a vacuum consumable arc furnace, and performs anti-oxidation treatment on the melt. This step can effectively remove impurities, greatly improve the purity of the alloy, ensure the stability of its chemical composition, and provide a solid foundation for the precise regulation of subsequent organizations. Then, in the forging and blanking stage, the smelted titanium ingot is heated to 100-160°C above the β phase transformation point and kept warm to make the organization uniform for the first recrystallization. In this process, the coarse grains in the cast state are broken under the combined action of high temperature and forging force, and transformed into relatively uniform equiaxed grains or deformed grains, dislocations are redistributed and partially annihilated, dislocation density is optimized, and the processing performance of the material is significantly improved. At the same time, it provides a good uniform initial organization for the hot rolling process, which is conducive to the uniform deformation and fine regulation of the organization during the hot rolling process. In the hot rolling stage, the billet is heated to the phase transition point (940℃) of the α+β two-phase region and rolled with the help of a four-roll reversible rolling mill. The α phase and the β phase are deformed synergistically under the rolling force, and the grains are elongated and flattened along the rolling direction to form a heterogeneous lamellar structure with uneven thickness. This lamellar structure not only produces a strengthening effect due to the increased resistance to dislocation movement at its interface, but also its unique organizational structure and stress distribution create extremely favorable conditions for subsequent deep cold rolling to induce twinning. Finally, multiple passes of deep cold rolling cause a large number of dislocations inside the titanium plate to multiply and interact with each other. When the dislocation density accumulates to a certain degree, high-density twins are formed under specific crystallographic conditions. Twins have high interface energy and stress field, which can effectively hinder the slip and proliferation of dislocations, thereby greatly improving the strength of the material. At the same time, the cold rolling process also promotes further grain refinement to form a coarse and fine mixed crystal structure, in which the fine-grained region strengthens the material by virtue of its larger grain boundary area, while the coarse-grained region plays a coordinating role in the deformation process, effectively ensuring the plasticity of the material, and ultimately achieving the synergistic strengthening and plasticity of coarse and fine mixed crystal heterogeneity and high-density twin structure.
[0016] (III) The present invention obtains TA18 titanium plates with coarse and fine mixed crystal heterogeneity and high-density twinning structure through a unique process, achieving a synergistic improvement in strength and plasticity. In the coarse and fine mixed crystal structure, fine grain strengthening and coarse grain coordinated deformation cooperate with each other, and high-density twins further strengthen the material and improve plasticity, successfully overcoming the difficult problem of balancing strength and plasticity of traditional titanium alloys, and making the material have excellent comprehensive mechanical properties. More importantly, the present invention eliminates the two annealing processes in traditional technology, thereby greatly reducing energy consumption, equipment use time, and labor costs. This not only significantly shortens the production cycle and improves production efficiency, but also shows outstanding economic advantages in industrial large-scale production, which is conducive to the wide promotion and application of products. Moreover, the two remelting smelting and fine processing technology control make the product structure more uniform and pure, the internal defects are greatly reduced, and the stability and reliability of product quality are greatly improved. It has a broader application prospect in high-end application fields such as aerospace and medical equipment that have extremely high requirements for material quality.
[0017] (IV) In contrast, the existing technology is not ideal due to the connection between the organizational evolution of each process. For example, the inhomogeneity of the structure after forging limits the full play of the subsequent process on material refinement and strengthening, resulting in limited improvement in the strength and plasticity of the final product, which is difficult to meet the current growing and stringent demand for high-performance titanium alloys. The high cost problem caused by multiple annealing processes puts it at a clear disadvantage in market competition, especially in large-scale industrial application scenarios that are extremely sensitive to cost. In addition, the complex process flow and relatively rough organizational control methods result in poor organizational uniformity of the final product, which may lead to large differences in local performance of the material during actual use, thereby affecting the overall performance and service life.
[0018] (3) The present invention uses consumable electrode blocks as raw materials, which has the following advantages: (a) The composition and microstructure of the raw materials can be controlled more accurately, thereby meeting the performance requirements of titanium plates for specific applications. (b) The raw material preparation process is simplified, the intermediate links are reduced, and the preparation efficiency is improved. (c) Although the initial cost of the consumable electrode blocks may be high, due to their high purity and uniform composition, the scrap rate and loss in subsequent processing can be reduced, thereby reducing the overall production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the preparation method of the present invention.
[0020] Figure 2 2(a) is the organizational diagram of the products obtained in Examples 1-4; 2(b) is the organizational diagram of Example 2, 2(c) is the organizational diagram of Example 3, and 2(d) is the organizational diagram of Example 4.
[0021] Figure 3 3(a) is the organizational diagram of the product obtained in Comparative Example 1-2, 3(b) is the organizational diagram of Comparative Example 2. DETAILED DESCRIPTION
[0022] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the protection scope of the present invention.
[0023] The present invention provides a short-process preparation method of a high-strength plastic titanium plate, which mainly comprises the following steps: Step 1: Place the TA18 titanium alloy consumable electrode block in a vacuum consumable arc furnace for two remelting smeltings. The first smelting voltage is 35V, the current is 2.5-3.5KA, and the vacuum degree is 1.0×10E-1Pa; the second smelting current is 4.0-5.0KA, the vacuum degree is 1.0×10E-1Pa, and then cast to obtain a pure TA18 titanium ingot. In terms of mass fraction, the composition of the TA18 titanium ingot is: 2.92% Al, 2.22% V, 0.025% Fe, 0.018% C, and the remainder is Ti and unavoidable impurities. The two remelting smeltings are used to perform anti-oxidation treatment on the molten alloy. This step can effectively remove impurities, greatly improve the purity of the alloy, ensure the stability of its chemical composition, and provide a solid foundation for the precise regulation of subsequent organizations. Step 2: Heat the TA18 titanium ingot to 100-160℃ above the β phase transition temperature for 1h, and then forge and open the blank, which can break the original coarse grains, refine them and evenly distribute them, and obtain a blank with a size of 120*500*5300mm. In this process, the coarse grains in the cast state are broken under the combined action of high temperature and forging force, and transformed into relatively uniform equiaxed grains or deformed grains. The dislocations are redistributed and partially annihilated, the dislocation density is optimized, the processing performance of the material is significantly improved, and good uniformity is provided for the hot rolling process. The initial organization is conducive to the uniform deformation and fine control of the organization during hot rolling; Step three, heat the billet to the phase transition point of the α+β two-phase region, use a four-roll reversible rolling mill for hot rolling, and roll the billet from 120.0mm to 5.8mm through 5-8 rolling passes. The single rolling deformation is not higher than 30%, and the total deformation is 95% to obtain a titanium alloy plate; dynamic recrystallization structure can be obtained through two hot rollings, and the α phase and β phase are deformed synergistically under the action of the rolling force. The grains are elongated and flattened along the rolling direction to form a heterogeneous lamellar organization with uneven coarseness and fineness. After rolling, the titanium alloy plate is surface polished and acid-alkali cleaned; Step 4: Soak the titanium alloy plate in liquid nitrogen for 20 minutes to 1 hour; perform deep cold rolling on the titanium alloy plate at 77K. After 4-6 rolling passes, the total rolling deformation is 17%-60%. It should be noted that the titanium alloy plate needs to be soaked in liquid nitrogen for 20 minutes to 1 hour before each rolling pass; multiple deep cold rolling passes cause the internal dislocations of the titanium plate to multiply and interact with each other. When the dislocation density accumulates to a certain extent, high-density twins will be formed, and finally a titanium plate with a thickness of 2.4 to 4.8 mm is obtained.
[0024] It should be noted that in step one, the preparation method of the TA18 titanium alloy consumable electrode block is: mixing sponge titanium, aluminum beans and aluminum vanadium according to the atomic percentage of Ti:Al:V=96:2.5:1.5, and then pressing the mixed raw materials into a cylindrical electrode block, and then welding the electrode block into a consumable electrode block.
[0025] The technical solution of the present invention is further explained and illustrated by embodiments below, however, such explanation and illustration do not constitute an improper limitation to the technical solution of the present invention.
[0026] Example 1
[0027] This embodiment provides a short-process preparation method for a high-strength plastic titanium plate, and the specific steps are as follows: Step 1: Send the TA18 titanium alloy consumable electrode block into a vacuum consumable arc furnace for two smeltings to obtain a TA18 titanium ingot. The vacuum degree in the furnace is 1.0×10E-1Pa. The melt is subjected to anti-oxidation treatment during the preparation process. The composition of the obtained titanium ingot is: 2.92% Al, 2.22% V, 0.025% Fe, 0.018% C, and the remainder is Ti and unavoidable impurities in the smelting process; Step 2: Heat the smelted titanium ingot to 100-160°C above the β phase transition temperature for 1 hour, and then forge and blank to obtain a blank with a size of 120*500*5300mm; Step 3: The billet is heated to the phase transition point (940°C) of the α+β two-phase region, and hot rolled using a four-roll reversible rolling mill to form a titanium alloy plate with a thickness of 5.8 mm. After rolling, the titanium plate is surface-polished and then cleaned with acid and alkali to remove the oxide layer. Step 4: Soak the titanium alloy plate in liquid nitrogen for about 20 minutes, and perform deep cold rolling at 77K. Before each rolling deformation, it needs to be soaked in liquid nitrogen to maintain a deep cold state. After rolling, a 4.8mm thick titanium plate is obtained, and the total rolling deformation is 17%.
[0028] Example 2
[0029] The difference between this embodiment and embodiment 1 is that in step 4, the total deformation of deep cold rolling is 25%, and the thickness of the titanium plate is 4.3 mm.
[0030] Example 3
[0031] The difference between this embodiment and embodiment 1 is that in step 4, the total deformation amount of deep cold rolling is 40%, and the thickness of the titanium plate is 3.5 mm.
[0032] Example 4
[0033] The difference between this embodiment and embodiment 1 is that in step 4, the total deformation amount of deep cold rolling is 60%, and the thickness of the titanium plate is 2.4 mm.
[0034] Comparative Example 1
[0035] This embodiment differs from Embodiment 1 in that step 4 is not included.
[0036] Comparative Example 2
[0037] The difference between this embodiment and embodiment 1 is that in step 4, room temperature rolling is adopted.
[0038] The titanium plates obtained in Examples 1-4 and Comparative Examples 1-2 were tested for microstructure, and the results are as follows: Figure 2 and Figure 3 shown. Figure 2 (a)-(d) are the organization diagrams of 17%, 25%, 40%, and 60% deformation in Examples 1-4. Figure 3 (a)-(b) are the organizational diagrams of comparative examples 1-2. Figure 2 and Figure 3 It can be seen that the plate subjected to dual-phase hot rolling and deep cold rolling has a coarse and fine lamellar heterogeneous structure, and the density of deformation twins increases with the increase of deformation amount.
[0039] The strength and plasticity of the titanium plates prepared in Examples 1-4 and Comparative Examples 1-2 were tested, and the results are shown in Table 1 below.
[0040] Table 1 Strength and plasticity test results of titanium plates prepared in Examples 1-4 and Comparative Examples 1-2 Yield strength / MPa Tensile strength / MPa Elongation / % Example 1 705 731 26.4 Example 2 864 889 25.1 Example 3 963 989 24.3 Example 4 996 1062 23.0 Comparative Example 1 551 650 21.6 Comparative Example 2 733 748 20.3
[0041] By comparing the above-mentioned Examples 1-4 and Comparative Examples 1-2, the multi-level heterogeneous structure titanium plate based on coarse and fine mixed crystals and twin crystal structures prepared in Example 1 has the most excellent strength-plasticity matching relationship.
[0042] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A short-process preparation method for high-strength plastic titanium plate, characterized in that: The main steps are as follows: Step 1: placing the TA18 titanium alloy consumable electrode block in a vacuum consumable arc furnace for two remelting smeltings, and then casting to obtain a pure TA18 titanium ingot; Step 2: Heat the TA18 titanium ingot to 100-160°C above the β phase transition temperature and keep it warm for 1 hour, then forge and open the blank to obtain a blank; Step 3, heating the billet to the phase transition point of the α+β two-phase region, hot rolling using a four-roll reversible rolling mill, rolling the billet from 120.0 mm to 5.8 mm through 5-8 rolling passes, with a single rolling deformation of no more than 30%, and a total deformation of 95%, to obtain a titanium alloy plate; after rolling, the titanium alloy plate is surface polished and acid-alkali cleaned; Step 4: Perform multiple passes of deep cold rolling on the titanium alloy plate to obtain a titanium plate with a thickness of 2.4 to 4.8 mm.
2. The short-process preparation method of a high-strength plastic titanium plate according to claim 1 is characterized in that: In step one, the preparation method of the TA18 titanium alloy consumable electrode block is: mixing sponge titanium, aluminum beans and aluminum vanadium according to the atomic percentage of Ti:Al:V=96:2.5:1.5, and then pressing the mixed raw materials into a cylindrical electrode block, and then welding the electrode block into a consumable electrode block.
3. The short-process preparation method of a high-strength plastic titanium plate according to claim 1 is characterized in that: In step 1, the first melting voltage is 35V, the current is 2.5~3.5KA, and the vacuum degree is 1.0×10E-1Pa; the second melting current is 4.0~5.0KA, and the vacuum degree is 1.0×10E-1Pa.
4. The short-process preparation method of a high-strength plastic titanium plate according to claim 1 is characterized in that: In step 1, the composition of the TA18 titanium ingot is, by mass fraction: 2.92% Al, 2.22% V, 0.025% Fe, 0.018% C, the balance is Ti and inevitable impurities.
5. The short-process preparation method of a high-strength plastic titanium plate according to claim 1 is characterized in that: In step 4, the specific method of deep cold rolling treatment of the titanium alloy plate is: immersing the titanium alloy plate in liquid nitrogen for 20 minutes to 1 hour; deep cold rolling treatment of the titanium alloy plate is performed under 77K conditions, and after 4-6 rolling passes, the total rolling deformation is 17%-60%.
6. A short-process preparation method for high-strength plastic titanium plate according to claim 5, characterized in that: Before each rolling pass, the titanium alloy plate needs to be immersed in liquid nitrogen for 20 minutes to 1 hour.
Citation Information
Patent Citations
High-temperature and high-strength titanium alloy and processing method thereof
CN112195364A
Cited By
Heat treatment-liquid nitrogen treatment-cryogenic forging composite forming method for obtaining alpha '+ alpha' biphase martensitic structure titanium alloy
CN120790811A